Prevalence of Tetanus in Adult Patient During one Year in Infectious Disease, Kabul Hospital, Afghanistan - Sharif, Mohammad Shafi; Sabawoon, Mohammad Naser (International Journal For Research In Biology & Pharmacy, 2020)
Tetanus quiet remains a major public health problem in Afghanistan like in most other developing countries, with a high morbidity and mortality. To study the demographic profile and the clinical profile that they presented with, as well as the outcome of the tetanus patients who were admitted to the Infectious, Disease Hospital, and Kabul Afghanistan. The data of all the patients of tetanus who were above the age of 15 years, who were admitted from March 2018 to March 2019, were collected, compiled and analyzed from the Medical Records of each case at Hospital. Out of the 23 cases of tetanus, 23 (100%) were males and 0 (0%) were females. Their ages varied from 25 to 35 years. The overall mortality rate was 52.17% and of 11 (47.82%) patients were cured. Regarding to occupation 18(78.26%) patient were farmer, 5(21.73%) were carpenter. Among all patient 21(91.3%) had positive history of inferior and superior extremities injury and remain 2(8.7%) had unknown history. None of the patients had taken tetanus immunization. The prevalence of adult tetanus and case fatality was consistent with the impact of routine and supplementary immunization activities. Although men were at high risk of tetanus infection, our analyses show that there is an underlying burden of tetanus among adolescent and adult men who have been largely missed by vaccination programs. In addition to strengthening tetanus toxoid immunization coverage, health education focusing on increasing awareness of NT could help reduce NT mortality.